1999
DOI: 10.1152/ajpcell.1999.276.6.c1303
|View full text |Cite
|
Sign up to set email alerts
|

ATP dependence is not an intrinsic property of Na+/H+exchanger NHE1: requirement for an ancillary factor

Abstract: Na+/H+exchange is a passive process not requiring expenditure of metabolic energy. Nevertheless, depletion of cellular ATP produces a marked inhibition of the antiport. No evidence has been found for direct binding of nucleotide to exchangers or alteration in their state of phosphorylation, suggesting ancillary factors may be involved. This possibility was tested by comparing the activity of dog red blood cells (RBC) and their resealed ghosts. Immunoblotting experiments using isoform-specific polyclonal and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Consistent with previous studies (21)(22)(23)(24)(25)(26)(27)(28), we find that pretreatment of CHO cells for 30 min with 5 mM 2-deoxy-D-glucose and 5 g͞ml oligomycin resulted in complete loss of NHE1 activity in subsequent recordings without addition of ATP to the pipette solution (data not shown). The omission of MgATP from the pipette solution alone, however, does not affect NHE1 activity.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous studies (21)(22)(23)(24)(25)(26)(27)(28), we find that pretreatment of CHO cells for 30 min with 5 mM 2-deoxy-D-glucose and 5 g͞ml oligomycin resulted in complete loss of NHE1 activity in subsequent recordings without addition of ATP to the pipette solution (data not shown). The omission of MgATP from the pipette solution alone, however, does not affect NHE1 activity.…”
Section: Resultssupporting
confidence: 93%
“…Grinstein and coworkers (20,(22)(23)(24)29) reported that NHE1 is sensitive to ATP depletion. ATP depletion must be quite extensive to inhibit NHE1, because the simple removal of ATP from the cytoplasmic solutions does not cause NHE1 rundown.…”
Section: Discussionmentioning
confidence: 99%
“…41 Because alanine, a noncarbohydrate source of energy, was able to abolish the inhibitory effect produced by the perfusion of 2-DG only in the absence of DL-cycloserine (an alanine aminotransferase inhibitor), we can assume that (1) 2-DG perfusion produced ATP depletion, which has been observed previously, 41 and (2) alanine is converted into pyruvate and can be used by the PT cells as an energy source. In addition, these data suggest that decreased glycolytic metabolism as well as ATP depletion might inhibit NHE3 in the PT.…”
Section: Discussionmentioning
confidence: 63%
“…38 In agreement with our findings, some studies have shown that glucose metabolism modulates other members of the NHE family. 9,31,[39][40][41][42][43][44] These transporters have been shown to be inhibited by glycolytic inhibitors, such as 2-DG, 9,45-47 and have also been observed to be more sensitive to glycolytic inhibitors than oxidative phosphorylation inhibitors. [48][49][50] Additionally, our study suggests, for the first time, that the apical uptake of glucose is important for maintaining NHE3 activity, because glucose was perfused only apically in the tubules, and that glucose metabolism occurs in the PT and is important for maintaining NHE3 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent intracellular acidification was expected to stimulate the Na + /H + exchanger NHE1, which is expressed in erythrocytes [85,86]. Activation of the carrier leads to entry of Na + and thus to cell swelling [87].…”
Section: Discussionmentioning
confidence: 99%